2005
DOI: 10.1021/ef049707n
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis in Asphaltene Precipitation and Redissolution

Abstract: The precipitation and redissolution of asphaltenes from mixtures of Athabasca bitumen and n-heptane was measured over time in both air and nitrogen atmospheres at 23 °C. In air, it appears that oxidation of the bitumen increased the asphaltene yield for as long as the experiments were conducted; that is, for several months. When oxidation effects are excluded, asphaltene precipitation and redissolution both appear to reach steady state within 24 h. A hysteresis between asphaltene precipitation and redissolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 16 publications
2
37
2
Order By: Relevance
“…In contrast, if the flocculation conditions remain close to the flocculation point, flocculation should be considered as reversible. In a recent study, Beck et al (2005) demonstrated hysteresis between asphaltene precipitation and redissolution. This effect is increased in the presence of air due to oxidation reactions.…”
Section: Flocculation Reversibility?mentioning
confidence: 98%
“…In contrast, if the flocculation conditions remain close to the flocculation point, flocculation should be considered as reversible. In a recent study, Beck et al (2005) demonstrated hysteresis between asphaltene precipitation and redissolution. This effect is increased in the presence of air due to oxidation reactions.…”
Section: Flocculation Reversibility?mentioning
confidence: 98%
“…The kinetics of asphaltene precipitation was measured for a variety of bitumens and crude oils in an air atmosphere and compared with the data collected in nitrogen previously reported by Duran et al 1 In nitrogen, the onsets and yields became invariant after 50 to 150 h, consistent with reaching an equilibrium condition. In air, the onsets and precipitation yields followed the same trend over time as in nitrogen for approximately 50 h but then deviated; in particular, the onsets decreased and the yields increased gradually over time for the 19 and k−1 and GM2 from Maqbool et al 2,29,57 The asphaltene contents are reported in Tables 1 and 5. duration of the experiments, consistent with the observations of Maqbool et al 2,29 The difference was attributed to oxygen, which likely alters the composition and reduces the solubility of the asphaltenes.…”
Section: Discussionmentioning
confidence: 87%
“…The mechanism was not investigated in this study but, as discussed previously, oxidation of the asphaltenes can occur even under ambient conditions and tends to reduce their solubility. 39 Figure 7 compares the yields from WC-B-B2 bitumen with yields from two other Western Canadian bitumens, all diluted with n-heptane under ambient conditions: (1) WC-B-A0, an Athabasca bitumen; 19 (2) WC-B-A3 (this study). Although the amount of precipitant required to obtain the same yield for each sample is different, the trends are the same for all three oils.…”
Section: Energy and Fuelsmentioning
confidence: 97%
See 1 more Smart Citation
“…Some authors have regarded asphaltene precipitation only as partially reversible [76], especially when asphaltenes are destabilised well beyond the onset conditions [77,78]. Apparent irreversibilities have also been associated with inappropriate reversibility criteria [79] and to the existence of an energy barrier to asphaltene dissociation [80]. In spite of the difficulties, the number of studies supporting reversibility is remarkable [74,75,[79][80][81][82][83].…”
Section: Introductionmentioning
confidence: 99%